1998
DOI: 10.1046/j.1365-2168.1998.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral colonization is unlikely to play an important role in Helicobacter pylori infection

Abstract: Oral colonization is a rare event, but does occur. Its rarity suggests that it is not an important factor in reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 8 publications
1
35
2
1
Order By: Relevance
“…This study investigated only adult patients. As H. pylori infection is mainly acquired in childhood [33], and the number of H. pylori in the mouths of adults is very low, this does not seem to be a signi®cant risk for hosts themselves [34,35]. According to a recent study, it seems likely that an infected mother may play a key role in transmission of H. pylori to her child, possibly via saliva [36].…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated only adult patients. As H. pylori infection is mainly acquired in childhood [33], and the number of H. pylori in the mouths of adults is very low, this does not seem to be a signi®cant risk for hosts themselves [34,35]. According to a recent study, it seems likely that an infected mother may play a key role in transmission of H. pylori to her child, possibly via saliva [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a fact that H. pylori has been detected in various dental samples, and there have been reports that paired strains from the mouth and stomach were identical (7,9). Oshowo et al (7) reported that oral colonization was a rare event, but did occur.…”
Section: Methodsmentioning
confidence: 99%
“…Today, it is considered to be a pathogen important to the development of gastrointestinal ulcers and it has been implicated as a carcinogen for gastric cancer and mucosa-associated lymphoid-tissue lymphoma of the stomach (2,3). H. pylori has been detected in dental plaque, saliva, and the subgingival region (4)(5)(6)(7)(8), and there have been reports that H. pylori strains in the mouth and stomach are identical (7,9,10). It has been suggested that the oral cavity might be an alternative reservoir for H. pylori (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…4 Human stomach is not the only reservoir of H. pylori and it has been detected in dental plaques, oral lesions, and saliva. 5 Recently, some researchers stated that H. pylori could play a role in the pathogenesis of various otorhinolaryngologic problems. It has been investigated in tonsils, adenoids, paranasal sinuses and in the middle ears of patients with chronic otitis media.…”
Section: Introductionmentioning
confidence: 99%